Rancang Bangun Game Edukasi Pembelajaran Aksara Jawa Berbasis Android - Margareta, Adhitya; Putra Eka Prismana, IGL; Setyo Permadi, Ginanjar (Inovate, 2021)
The written communication tool used by the Javanese tribe is Javanese script. Javanese script education is important to be taught to children from an early age so that children are not blind to Javanese script itself and to support the preservation of the nation's culture. The purpose of this research is to build Javanese script learning educational games for children, as well as to help the government in preserving local culture. The method used in this game is the Decision Tree and Finite State Machine (FSM) method. Decision Tree is used as an assessment or scoring in the game. The steps of the Decision Tree method are to determine the first parameter that will be used as the highest score to be obtained, the next step is to determine the second parameter that will be used as the score, and so on. The Finite State Machine (FSM) works based on the results obtained from the previous decision tree calculations, which will determine the continuation of the game. The results of this study are a Javanese script educational game for Javanese script learning in the form of connecting dots to become a script. Java, so players can play while learning. Keywords: Game, Javanese Script, Finite State Machine (FSM), Decision Tree